Answer:
6x + 1
Step-by-step explanation:
1. (10x + 3) + (-4x -2) --> sum means to add.
2. Combine like terms --> 10x - 4x = 6x; 3 - 2 = 1.
3. 6x + 1
Step-by-step explanation:
given
![y = 3x + 4](https://tex.z-dn.net/?f=y%20%3D%203x%20%2B%204)
![y(2) = 3(2) + 4 \\ = 6 + 4 = 10](https://tex.z-dn.net/?f=y%282%29%20%3D%203%282%29%20%2B%204%20%5C%5C%20%20%3D%206%20%2B%204%20%3D%2010)
Answer:
3 down, 4 up
Step-by-step explanation:
-3 is the X line, which starts on 0, if you subtract 3, or add -3, you would have to go down, 3 down. 4 is on the Y line, so you add, go left to add on the Y line, 4 up.
Always start with you X coordinate. Here is a tip to help you (X, Y)
The answer is b. The Remainder<span> Theorem says that if a polynomial </span>f(x<span>) is divided by </span>x<span> – k, then </span>the remainder<span> is </span>f(k). k=3 in our case, so the remainder is simply f(3). Plug in x=3 into <span>f(x) = 7x4 + 12x3 + 6x2 - 5x + 16. f(x)=946. So the answer is b.</span>